On the Time-Varying Effects of Economic Policy Uncertainty on the US Economy - Jan Prüser; Alexander Schlösser (Oxford Bulletin of Economics and Statistics, 2020)
We study the impact of Economic Policy Uncertainty (EPU) on the US Economy by using a VAR with time-varying coefficients. The coefficients are allowed to evolve gradually over time which allows us to discover structural changes without imposing them a priori. We find three different regimes, which match the three major periods of the US economy, namely the Great Inflation, the Great Moderation and the Great Recession. The initial impact on real GDP ranges between -0.2% for the Great Inflation and Great Recession and -0.15% for the Great Moderation. In addition, the adverse effects of EPU are more persistent during the Great Recession providing an explanation for the slow recovery. This regime dependence is unique for EPU as the macroeconomic consequences of Financial Uncertainty turn out to be rather time invariant.
Keywords: 330